Problemy związane z deﬁnicją lasu w polskim systemie prawnym - Bujny, Jędrzej; Mądry, Tymoteusz (Studia Prawa Publicznego, 2019)
The article touches upon the controversies around the deﬁ nition of a forest contained in the provision of Article 3 of the Act of 28 September 1991 on forests, present in the doctrine as well as in judicial decisions in administrative law. The interpretation of the above provision is analysed and the views presented in the doctrine and the judicial rulings, which sometimes include contradicting arguments, are examined. In the ﬁ rst part of the article individual elements of the deﬁ nition of a forest have been identiﬁ ed and the diffi culties with their interpretation that have led to the emergence of a vast number of judicial decisions and rulings delivered by administrative courts as well as the Supreme Court have been presented. The second part contains deliberations on the importance of the data included in the land and buildings register and their potential use for the classiﬁ cation of land as a forest on the grounds of concrete administrative proceedings, including these on tax matters. In this context the normative value of the provisions of the Act of 17 May 1989: Geodetic and Cartographic Law and individual tax laws making these data binding and applicable has been examined as well. Also this latter issue generates frequently diverging opinions expressed by administrative courts. The last part of the paper contains de lege lata and de lege ferenda postulates intended to reconcile the presented controversies connected with the classiﬁ cation of individual land as forest. The authors hope that implementation of these postulates will contribute to the uniﬁ cation of the judiciary opinions regarding the concept of a forest and consequently will help to eliminate the existing doubts.